Predictors of long‐term outcome in multiple sclerosis patients treated with interferon beta. Issue 1 (1st February 2013) - Bermel, Robert A.; You, Xiaojun; Foulds, Pamela; Hyde, Robert; Simon, Jack H.; Fisher, Elizabeth; Rudick, Richard A.
Abstract: Objective: To identify early predictors of long‐term outcomes in patients with relapsing–remitting multiple sclerosis (RRMS) treated with intramuscular (IM) interferon beta‐1a (IFNβ‐1a). Methods: A multicenter, observational, 15‐year follow‐up study of patients who completed ≥2 years in the pivotal trial of IM IFNβ‐1a for RRMS was conducted. One hundred thirty‐six patients participated in the 15‐year follow‐up (69 originally randomized to IM IFNβ‐1a and 67 to placebo). After the 2‐year clinical trial, treatment was not regulated by study protocol. Disease activity during the 2‐year trial was defined as: ≥2 gadolinium‐enhancing lesions (cumulative) on year 1 and/or year 2 magnetic resonance imaging (MRI); ≥3 new T2 lesions on year 2 MRI compared to baseline; and ≥2 relapses over 2 years. Odds ratios were calculated for early disease activity predicting severe Expanded Disability Status Scale (EDSS) worsening (worst quartile of change, ≥4.5 EDSS points) during the 15‐year interval. Results: The proportion of patients experiencing early disease activity was lower in patients on IM IFNβ‐1a than placebo for all disease activity markers (range, 23.5–29.0% vs 41.0–45.5%). In the IM IFNβ‐1a group, persistent disease activity predicted severe EDSS worsening: gadolinium‐enhancing lesions (odds ratio [OR], 8.96; p < 0.001); relapses (OR, 4.44; p = 0.010); and new T2 lesions (OR, 2.90; p = 0.080). In placebo patients, early disease activity was not as strongly associated with long‐term outcomes (OR range, 1.53–2.62; p = 0.069–0.408). Interpretation: Disease activity despite treatment with IFNβ is associated with unfavorable long‐term outcomes. Particular attention should be paid to gadolinium‐enhancing lesions on IFNβ therapy, as their presence strongly correlates with severe disability 15 years later. The results provide rationale for monitoring IFNβ‐treated patients with MRI, and for changing therapy in patients with active disease. ANN NEUROL 2013.